Effective Metacognitive Strategy Factors on the Reading Comprehension of the Iraqi Female Students (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This paper addresses issues on educational process and reading comprehension. These factors are influenced by the aspect of metacognition as well as reading strategy awareness. When students are facing challenges in their reading ability, researchers often suggest the application of this strategy. Language learning places emphasis on this aspect this study looks at the metacognitive reading strategies and it strikes to find out what are the factors that affect female students in Iraq towards reading comprehension. Quantitative research design was employed in this study. Specifically, a quasi-experimental approach was applied to collect data from fifty students through the questionnaire tool. The data of this study was analysed using SPSS 25 software. The major findings revealed that metacognitive knowledge and use of strategies are some of the essential factors that will improve students’ reading ability and performance. However, planning and management are totally not part of the expected result. Educators should be conversant with the advent of new technologies that seek to enhance reading comprehension among students and females, especially in order to overcome some of these learning challenges. The study concludes that female students need to be given special attention against their males’ counterpart in order to wipe out the reading and comprehension challenges.